The Establishment of Customer Loyalty in View of Service Quality and Bank Reputation - Hardyansah, Rommy; Jahroni, Jahroni (Bulletin of Science, Technology and Society, 2023)
This study aims to analyze the effect of service quality and bank reputation on customer loyalty. This research was conducted using quantitative methods. Data collection was carried out through questionnaires which were distributed via google form to 120 customers of the Indonesian state bank (BNI). The collected data were analyzed using descriptive statistical techniques and multiple linear regression analysis. The results of this study indicate that the quality of bank services has a positive and significant impact on customer loyalty. Customers tend to be more loyal to banks that provide high-quality services, including ease of transaction, speed of service, good personal interaction, and effective response to customer complaints. In addition, the bank's reputation also has a positive and significant influence on customer loyalty. Customers are more likely to remain loyal to a bank with a good reputation, which includes integrity and public trust.